The effects of iodine blocking on thyroid cancer, hypothyroidism and benign thyroid nodules following nuclear accidents: a systematic review. (21st September 2016) - Pfinder, M; Dreger, S; Christianson, L; Lhachimi, S K; Zeeb, H
Abstract: A potential radiation protection method to reduce the risk of adverse health outcomes in the case of accidental radioactive iodine release is the administration of potassium iodide (KI). Although KI administration is recommended by WHO's Guidelines for Iodine Prophylaxis following Nuclear Accidents, a systematic review of the scientific evidence for the guidelines is lacking. Therefore, this study aims to systematically review the effects of KI administration in the case of accidental radioactive iodine release on thyroid cancer, hypothyroidism and benign thyroid nodules. We applied standard systematic review methodology for a search of the literature, selection of eligible studies, data extraction, assessment of risk of bias, assessment of heterogeneity, data synthesis, and the assessment of the quality of the evidence. We searched MEDLINE (via PubMed) and EMBASE. We found one cross-sectional study, one analytic cohort study and two case-control studies relating to our question. The number of participants ranged from 886–12 514. Two studies were conducted in children and two other studies in children and adults. It was not possible to conduct a meta-analysis. We identified low to very low-quality evidence that KI administration after a nuclear accident resulted in a reduction of the risk of thyroid cancer in children; however, the KI administration and dose was not well described in the studies. None of the studies investigated the effects of KI administration in the case of a nuclear accident on hypothyroidism and benign thyroid nodules. Low to very low-quality evidence suggests that KI intake following a nuclear accident may reduce the risk of thyroid cancer in children. No conclusions can be drawn about the effectiveness of KI intake with respect to the prevention of hypothyroidism and benign thyroid nodules.